HUBUNGAN PENDIDIKAN DAN PELATIHAN TERHADAP KOMPETENSI PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN KAMPAR - Iman Perama; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
In order to regional autonomy necessary apparatus that qualified, skilled in order to carry out the task of the government, and the services to the people that satisfies. But a staff of Education and Culture Kampar Regency at this time we still have any minus and weakness this can be known from the phenomenon that I come across. Human resources Looking, indirectly will can have an effect on the performance of Education and Culture Kampar Regency, So that I'm formulate this research is whether there is a relationship between education and training to employee's competency in the Education and Culture Kampar Regency in the service to the community. To answer the purpose of this research, I'm doing an assessment data using questionnaires and carry out a study libraries or documents from the office of Education and Culture Kampar Regency. Analytical technique data using multiple regression and correlation Spearmans' Rho. This research that there were positive relationships together and education, training and the competence is expected to be given. opportunity Iuasnya for civil servants to improve their competence, through its participation in technical training in relation to task implementation dang function, among other training Quality Management, Training Center of Intellectual Property Rights and others.Key words : Relationship, Education, Training, Competence, Civil Servants